Analysis And Comparing The Effect Of Financial Ratios On Stock Returns Of Automotive And Components Companies Listed In Indonesia Stock Exchange And Taiwan Stock Exchange - Permatasari, Sheila Silvia; Chen, Jun Hong; Julito, Kiko Armenita (Jurnal Akuntansi Manajerial, 2025)
This study aims to determine the effect of financial ratios on stock returns in automotive sector companies and components listed on the Indonesia Stock Exchange and Taiwan Stock Exchange for the 2018-2022 period. It finds out how financial ratios influence stock returns in the years before covid, during covid, and after covid. Through this research, it can also be seen how the situation in these two countries, especially with the limited circumstances in the era of the Covid-19 pandemic. This research is a documentation study, where the data used are secondary data obtained from available company reports. The population in this study is all companies in the automotive sector and components listed on the IDX and TWSE in a predetermined period. A total of 12 companies were taken from the IDX and 27 companies were taken from the TWSE. The results show that from Indonesian data, EPS has a positive and significant effect on stock returns. ROA has a negative and significant effect on stock returns. CR, TATO, ROE, and PER have a positive and insignificant effect on stock returns. DER and ITO have a negative and insignificant effect on stock returns. Meanwhile, from Taiwan data, CR and DER have a positive and significant effect on stock returns. ROE has a negative and significant effect on stock returns. TATO, ROA, and EPS have a positive and insignificant effect on stock returns. ITO and PER have a negative and insignificant effect on stock. In addition, there is no significant difference on the regression coefficient between Indonesia and Taiwan based on the Chow test.